The Impact of Teachers’ Leadership on Students’ Achievements in Private Schools in the Emirate of Abu Dhabi - AL KAFRI, YOUSEF ALI (2024)
The present research explores the conceptual framework that underlines the impact of teachers’ leadership on students’ achievements and non-cognitive skills in private schools in the Abu Dhabi Emirate. Examining well-known leadership theories, such as transformational, transactional, instructional, and distributed, helps one to investigate the theoretical underpinnings of those inspiring leadership, to address the pressing need to understand how such leadership influences corporate culture, motivates teachers, and increases student engagement. The study aims to grasp the intricate mechanisms by which various leadership styles influence organizational dynamics and student achievements in private schools by combining a variety of theoretical perspectives. The research employs a mixed-methods approach, utilizing both quantitative surveys and qualitative semi-structured interviews to gather comprehensive data from teachers, students, and school leaders. Motivated by the main research question, “What impact does teachers’ leadership have on students’ academic achievement in private schools within the Abu Dhabi Emirate?” the study, for example, shows that transformational leadership is quite important in determining organizational culture, motivating teachers, and raising student involvement. These results support future empirical research projects and add to the scholarly debate on educational leadership. Furthermore, the research offers useful information for creating successful leadership plans in Abu Dhabi and surrounding schools. In order to underline the need for more research and application in educational practices, the study finally shows that transformational, instructional, transactional, and distributed leadership styles have great potential to positively influence students’ achievements and non-cognitive skills.